2019
DOI: 10.1590/0100-29452019997
|View full text |Cite
|
Sign up to set email alerts
|

Dwarfing-canopy and rootstock cultivars for fruit trees

Abstract: As fruit trees generally have a large size, the production of small or even dwarf trees is of great interest for most of fruit crops. In this review, some of the main tropical, subtropical and temperate fruit trees that have small or even dwarfing cultivars are approached. The causes of dwarfism, although the use of dwarfing rootstocks, is the main theme of this review. The factors that affect the size of the fruit trees are also approached, as well the dwarf cultivars of banana, papaya and cashew, and the dwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 10 publications
0
23
0
6
Order By: Relevance
“…Although earliness is a characteristic of the scion, the rootstock may change the ripening development of orange fruits [30,33,35]; thus, rootstock selection plays a crucial role in new citrus orchards. The rootstock is an important component of a healthy and productive citrus tree, influencing the fruit yield, fruit quality, tree size, and tolerance of diseases [60,61].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although earliness is a characteristic of the scion, the rootstock may change the ripening development of orange fruits [30,33,35]; thus, rootstock selection plays a crucial role in new citrus orchards. The rootstock is an important component of a healthy and productive citrus tree, influencing the fruit yield, fruit quality, tree size, and tolerance of diseases [60,61].…”
Section: Resultsmentioning
confidence: 99%
“…When grafted on 'Trifoliata' hybrid rootstocks, orange trees produce high-quality fruit with desirable attributes for the juice industry, such as high SS content and juice yield [20,23,[30][31][32][33]. 'Swingle' is the best-known citrumelo in Brazil and globally.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers reported that citrus scion grafted on Citrumelo and Rangpur lime had the same canopy volume (Gonzatto et al 2011;Bacar et al 2017). The use of Fortunella as rootstock caused tree size and canopy volume of citrus scion smaller than other rootstocks (Ono and Hirose 1987;Donadio et al 2019). However, the Fortunella is a subtropical citrus, adaptation within the tropical area such as in Indonesia is still to be examined.…”
Section: Discussionmentioning
confidence: 99%
“…Citrumelo is tolerant to Citrus Tristeza Virus (CTV) (Castle et al, 2000), nematodes, Phytophthora spp., CSD (Bové and Ayres, 2007) and cause the superior fruit quality of scion. The use of Fortunella as rootstock caused tree size and canopy volume of citrus scion smaller than other rootstock (Donadio et al, 2019). Unfortunately, there is still no study of the effect of rootstocks on the physiology of citrus plants in Indonesia.…”
Section: Introductionmentioning
confidence: 99%